The reaction specificity of mammalian ALOX15B orthologs does not depend on the evolutionary ranking of the animals - Eda Gündem; Sabine Stehling; Astrid Borchert; Hartmut Kuhn (Journal of Lipid Research)
Arachidonic acid lipoxygenases (ALOXs) play important roles in cell differentiation and in the pathogenesis of cardiovascular, hyperproliferative, neurodegenerative, and metabolic diseases. The human genome involves six intact ALOX genes and knockout studies of the corresponding mouse orthologs indicated that the coding multiplicity of ALOX isoforms is not an indication for functional redundancy. Despite their evolutionary relatedness human and mouse ALOX15 and ALOX15B orthologs exhibit different catalytic properties. Human ALOX15 oxygenates arachidonic acid mainly to 15S-hydroperoxy-5Z,8Z,11Z,13E-eicosatetraenoic acid but 12S-hydroperoxy-5Z,8Z,10E,14Z-eicosatetraenoic acid is the dominant oxygenation product of mouse Alox15. This functional difference is the results of a targeted enzyme evolution but the driving forces for this process have not been well defined. For human and mouse ALOX15B orthologs similar functional differences have been reported but for the time being it was unclear whether these differences might also be a consequence of targeted enzyme evolution. To address this question, we systematically searched the public databases for ALOX15B genes, expressed selected enzymes, and characterized their functional properties. We found that functional ALOX15B genes frequently occur in Prototheria and Eutheria but orthologous genes are rare in Metatheria. The vast majority of mammalian ALOX15B orthologs constitute arachidonic acid 15-lipoxygenating enzymes and this property did not depend on the evolutionary ranking of the animals. Only several Muridae species including M. musculus, M. pahari, M. caroli, M. coucha, and A. niloticus express arachidonic acid 8-lipoxygenating ALOX15B orthologs. Consequently, the difference in the reaction specificity of mouse and human ALOX15B orthologs may not be considered a functional consequence of targeted enzyme evolution.